Assessment of the self‐healing capacity of cementitious materials through active thin sections. (28th December 2021) - Rossi, Emanuele; Romero Rodriguez, Claudia; Jonkers, Henk; Çopuroğlu, Oğuzhan
Abstract: Since self‐healing of cementitious materials can theoretically improve the service‐life of concrete structures, it has gathered significant attention from both researchers and industry during the last two decades. Many researchers have proposed different methods to assess and quantify the self‐healing capacity (i.e. the ability of cementitious materials to heal cracks) that is generated in concrete autogenously as well as autonomously. Even though many methodologies can be found in the literature, a way to accurately quantify the healing products produced by any self‐healing mechanism has not been yet achieved. In this study, a methodology is proposed to observe and to quantify in‐time formation of healing products based on active thin sections. Thin sections of Portland cement paste have been prepared with no epoxy impregnation to facilitate reactions between the cement matrix and the surrounding environment. Artificial cracks (260 μm wide) were induced at 28 days of age and the crystal growth was continuously monitored up to 28 days of self‐healing. Through image analysis of the micrographs, it was calculated that the autogenous self‐healing capacity of paste (triggered by portlandite carbonation in uncontrolled indoor conditions) was around 55% after 28 days of self‐healing. Healing products were further characterised through Environmental Scanning Electron Microscope analysis. Based on the results obtained in this study, the proposed methodology seems to be promising to compare the self‐healing mechanisms triggered by different healing agents.